3-Phenylpropanoic Acid Improves the Affinity of Ruminococcus albus for Cellulose in Continuous Culture - Morrison, Mark (1990)
A continuous-culture device, adapted for use with solid substrates, was used to evaluate the effects of 3-phenylpropanoic acid (PPA) upon the ability of the South African strain Ruminococcus albus Ce63 to ferment cellulose. Steady states of fermentation were established with a dilution rate of 0.17 h(−1), and the extent and volumetric rates of cellulose fermentation were determined over four consecutive days. When the growth medium contained no additions (control), 25 μM phenylacetate alone, 25 μM PPA alone, or 25 μM each of phenylacetate and PPA, the extent of cellulose hydrolysis was determined to be 41.1, 35.7, 90.2, and 86.9%, respectively, and the volumetric rate of cellulose hydrolysis was 103.0, 97.9, 215.5, and 230.4 mg liter(−1) h(−1), respectively. To evaluate the effect of PPA availability on affinity for cellulose, the values for dilution rate and extent of cellulose hydrolysis were used in combination with values for maximum specific growth rate determined from previous studies of growth rates and kinetics of cellulose hydrolysis. The findings support the contention that PPA maintains a competitive advantage for R. albus when grown in a dynamic, fiber-rich environment.